2002
DOI: 10.1099/00221287-148-6-1637
|View full text |Cite
|
Sign up to set email alerts
|

The complete nucleotide sequence and environmental distribution of the cryptic, conjugative, broad-host-range plasmid pIPO2 isolated from bacteria of the wheat rhizosphere The GenBank accession number for the pIPO2T sequence reported in this paper is AJ297913.

Abstract: Plasmid pIPO2 is a cryptic, conjugative, broad-host-range plasmid isolated from the wheat rhizosphere. It efficiently self-transfers between α, β and γ Proteobacteria and has a mobilizing/retromobilizing capacity for IncQ plasmids. The complete nucleotide sequence of pIPO2 is presented on the basis of its mini-Tn5 ::luxABtet-tagged derivative, pIPO2T. The pIPO2 sequence is 39 815 bp long and contains at least 43 complete ORFs. Apart from a suite of ORFs with unknown function, all of the genes carried on pIPO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 88 publications
(52 reference statements)
1
124
0
5
Order By: Relevance
“…For example, a 45 kb cryptic plasmid belonging to a new family was isolated based only on its ability to mobilize a resistance plasmid, a general property shared by most conjugative plasmids. This plasmid, pIPO2T, is widespread in rhizosphere populations and contains a suite of ORFs with unknown functions in addition to genes predicted to be involved in plasmid replication, maintenance and conjugative transfer (Tauch et al 2002). In other studies, an ingenious transposon capture method was used to isolate nonspecific plasmid DNA from the human gut flora, thereby recovering several small cryptic plasmids (Jones & Marchesi 2007), and a PCR-based method was used to amplify and sequence environmental ORFs related to class 1 integrons (Stokes et al 2001).…”
Section: How Do We Study the Communal Gene Pool?mentioning
confidence: 99%
“…For example, a 45 kb cryptic plasmid belonging to a new family was isolated based only on its ability to mobilize a resistance plasmid, a general property shared by most conjugative plasmids. This plasmid, pIPO2T, is widespread in rhizosphere populations and contains a suite of ORFs with unknown functions in addition to genes predicted to be involved in plasmid replication, maintenance and conjugative transfer (Tauch et al 2002). In other studies, an ingenious transposon capture method was used to isolate nonspecific plasmid DNA from the human gut flora, thereby recovering several small cryptic plasmids (Jones & Marchesi 2007), and a PCR-based method was used to amplify and sequence environmental ORFs related to class 1 integrons (Stokes et al 2001).…”
Section: How Do We Study the Communal Gene Pool?mentioning
confidence: 99%
“…Together, these findings suggest that parts of chromosome 2 may have been originally acquired from a plasmid. The recent identification of the closest sequenced homologs to date of the Brucella virB genes on conjugative plasmids from microbes of the rhizosphere of wheat and alfalfa lends further support to this idea (31,32).…”
mentioning
confidence: 78%
“…Plasmid pIPO2 was isolated in R. eutropha based on its mobilizing capacity. Replicon typing and sequencing of the complete plasmid (Tauch et al, 2002) revealed that this cryptic plasmid of a size of approx. 45 kbp was not related to any of the known BHR plasmids except to plasmid pSB102 (Schneiker et al, 2001).…”
Section: Mges In Bacterial Communities Of Agricultural Settings Prevamentioning
confidence: 99%